Effects of two different variants in the MAGT1 gene on B cell subsets, platelet function, and cell glycome composition - del Pino Molina, Lucía; Monzón Manzano, Elena; Gianelli, Carla; Bravo Gallego, Luz Yadira; Bujalance Fernández, Javier; Acuña, Paula; Soto Serrano, Yolanda; Reche Yebra, Keren; Bravo García-Morato, María; Sánchez Zapardiel, Elena; Arias-Salgado, Elena G.; Rodríguez Pena, Rebeca; et al. (Frontiers in Immunology, 2025)
IntroductionX-linked immunodeficiency with magnesium defect, Epstein-Barr virus (EBV) infection and neoplasia (XMEN) disease is caused by hemizygous loss of function (LOF) gene variants in MAGT1. MAGT1 is a plasma membrane transporter of magnesium (Mg2+) that plays a relevant role in immune responses and acts as a second messenger in intracellular signaling, but also it is involved in the glycosylation of proteins. Here we report two gene variants in the MAGT1 gene from two different families with XMEN disease. A de novo variant c.97_98 delinsC affecting one member of one family and three members of a second family presented the hemizygous variant c.80``3G>A, p.Trp268Ter, causing a premature stop codon.MethodsWe performed a functional validation of these two variants in the MAGT1 gene and their association with decreased NKG2D expression, uncontrolled EBV viremia, and the development of lymphoma-associated complications in three members of the same family.ResultsWe analyzed the B-cell compartment, we found that the B-cell expansion is driven by immature/transitional (CD5- and CD5+) and naïve B cells. The patients presented normal absolute counts of memory B-cells (MBCs) but with differences between them in the diversity of immunoglobulin heavy chain (IgH) isotype distribution in MBC, and diverse reduction of plasma cells. We also explored the alterations of platelets due to hemorrhagic events and a history of thrombocytopenia in some of our patients. We found diminished TRAP-induced calcium flux, P-selectin and CD63 exposure in XMEN patients, while when platelets from patients were stimulated ADP the results were similar to healthy controls. Finally, we explored the glycosylation pattern in platelets and lymphocytes. Our results suggest that different variants in MAGT1 gene might result in different effects on NK cells and platelet glycome composition.DiscussionHere, we report the two different outcomes regarding EBV-driven lymphoproliferative complications, the family with three members affected that developed the malignant lymphoproliferative complications before XMEN diagnosis, and the patient with early diagnose of MAGT1 deficiency due to EBV viremia. As a recommendation, XMEN disease should be ruled out in males with impaired clearance of EBV-infection and EBV-driven lymphoproliferative complications.